KEBIJAKAN HUKUM PIDANA DALAM PEMBERANTASAN ILLEGAL UNREPORTED AND UNREGULATED FISHING DI INDONESIA - Fanny Ayunda Dwi Putri; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia is a state of law as stated in Article 1 Paragraph 3 of the 1945 Constitution of theRepublic of Indonesia. Indonesia has an area of 5,455,675 km2 and 3,544,744 km2 of which or 2/3 of itsterritory is the ocean. Indonesia has a diversity of natural resources both biological and non-biological.Especially the living natural resources in the sea which are the biggest assets owned by Indonesia so thatit is necessary to regulate the management and legal protection related to illegal, unreported, andunregulated fishing problems due to the rampant cases that occur in Indonesia related to illegal fishing.thus causing substantial losses to Indonesia. In Law Number 31 of 2004 jo. Law No. 45 of 2009concerning Fisheries strictly regulates matters relating to the management and legal protection ofcriminal acts relating to illegal, unreported, and unregulated fishing.The purpose of this study is to analyze criminal law policies in eradicating illegal, unreported,and unregulated fishing in Indonesia. The research method used in this paper is normative legalresearch, legal research conducted by examining library materials or secondary data, can be callednormative legal research or library legal research. This study uses methodologies for legal principles.Criminal law policies in eradicating illegal, unreported, and unregulated fishing in Indonesia are veryimportant regulations to minimize the occurrence of crimes in the context of fisheries in Indonesia andare a shared responsibility of the community and other law enforcement officials so that theirsustainability can be maintained. We really need clear regulations and have very strict legal certaintyagainst criminal sanctions and other sanctions that will cause a deterrent effect on perpetrators offisheries crimes.Keywords: criminal law policy, illegal fishing, unreported, unregulated fishing.